Surgical Management of Non-Obstetric Acute Abdomen During Pregnancy: A Retrospective Review of 24 Cases After 8-Years’ Experience - Turğal, Mert; Yazıcıoğlu, Aslıhan; Beksaç, Kemal; Aran, Ömer; Abbasoğlu, Osman; Kaynaroğlu, Volkan; Özyüncü, Özgür; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2012)
Objectives: Diagnosis and management of non-obstetric acute abdomen during pregnancy is a cause of concern both for the obstetricians and the general surgeons. A resistance against operation during pregnancy leads to unnecessary delay which may increase both maternal and fetal morbidity, even mortality. In this study we present our experience in surgical management of pregnant patients with non-obstetric acute abdomen. Study Design: Pregnant patients with acute abdomen requiring surgical exploration were enrolled from 2004 to 2012. Women were excluded from the analysis if the surgical procedure was obstetric in nature. Demographics, gestational age, symptoms, operative results, postoperative complications, pregnancy outcome and imaging studies were assessed. Results: There were 24 patients with a mean age of 28,25±3.51 years. Operations are often performed in the second trimester. Most common symptoms were abdominal pain (100%) and nausea (83%). Ovarian torsion and appendicitis were the most common etiologies causing non-obstetrical acute abdomen (33% and 25%, respectively). All patients tolerated surgery well, 11 of them had no postoperative complications, however 3 fetal losses, 4 preterm deliveries, 3 PPROM, 1 re-operation and 1 vaginal bleeding were observed. One patient died from acute respiratory distress syndrome in the 24th day of the surgery. Ultrasonography was performed in 22 patients, MR imaging was used in 11 patients. Sonographic findings were diagnostic in 59%, while MR was successful in assigning the correct diagnosis in 100%. Conclusions: The issue of surgical management of non-obstetric acute abdomen during pregnancy is an important concern for clinicians who care women. Prompt diagnosis and appropriate surgical approach are the cornerstones of the management. Due to the diagnostic limitations of ultrasonography, MR imaging has become increasingly popular and gave direction to management strategy.